Research and development abroad: German companies focus on strengths similar to those at home - Heike Belitz; Anna Lejpras; Maximilian Priem (DIW Weekly Report, 2019)
More than one in four patents that major German companies apply for is based on inventions from their research laboratories abroad. In three quarters of the cases, the companies have focused on technologies in which they are very strong at home. Therefore, to a great extent the technological research and development performance at their home location determines the innovative power of globally active German companies. As the present report also shows, based on patent data, most foreign research activities abroad either supplement domestic activities or support sales and production abroad. Internationalization strategies intended to compensate for technological deficits at home have a lower proportion. German companies in the information and communication technology industries, whose importance is increasing in the wake of digitalization, are the primary implementers of such strategies. To better be able to acquire and use the knowledge companies gain abroad, the research in these technological fields of the future should be strengthened in Germany as well. As a research location, Germany can benefit from the continuing internationalization of its globally active companies if public research, at universities for example, can expand their technological basis and remain attractive cooperation partners to said companies.
Keywords: D24; F21; L60; O31; 330; R&D; Patents; Globalisation; German Multinationals